If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = -2x + 46 Reorder the terms: 12 = 46 + -2x Solving 12 = 46 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 12 + 2x = 46 + -2x + 2x Combine like terms: -2x + 2x = 0 12 + 2x = 46 + 0 12 + 2x = 46 Add '-12' to each side of the equation. 12 + -12 + 2x = 46 + -12 Combine like terms: 12 + -12 = 0 0 + 2x = 46 + -12 2x = 46 + -12 Combine like terms: 46 + -12 = 34 2x = 34 Divide each side by '2'. x = 17 Simplifying x = 17
| x^2+2x+3=4.25 | | 5a+c=-8m | | 4t-2=10 | | .03(7g-9)=7-2g | | 9x+y=3y-7 | | 3(n-1)=4(4f-8) | | x+y+6=12 | | 7z=48 | | -4z=14-5z | | -4z=14-5 | | (3x+7)=7x+15 | | -512=-8n+8(-8+8n) | | 5y^2-33y+18=0 | | -3-4x=1.5x-2 | | 6x+2=2x+5 | | -30=-3x | | 4.2x-0.88=1.68-2.2x | | 4x+2=-3x+4 | | a-9=132 | | 3*8-9=12-2*8 | | 5(3+3x)-5=85 | | P-15=54 | | 23x-7-17x+4=17x-4-11x+16 | | 13+3n=8n-3(n-4) | | 3x-9=12-2x | | -3(p+7)=21 | | 3(12w+4)= | | (3W^2-5W)-[(w^2+5w)-(4W^2-2w)]= | | -2(2f-4)=-4(-f+4) | | 18-(5m+3)=5+4m-17 | | 145-(6x+12)=6(x+7)+x | | 4p^2-21p-18=0 |